2012
DOI: 10.18097/pbmc20125805599
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry detection of monomeric renalase in human urine

Abstract: Renalase is a recently discovered secretory protein, which is suggested to play a role (which still remains elusive) in regulation of blood pressure. Earlier it was purified from urine of healthy volunteers by means of ammonium sulfate fractionation and subsequent affinity chromatography (Xu et al. (2005) J. Clin. Invest., 115, 1275). The resultant purified preparation of renalase contained 2 proteins with molecular masses of 35 and 67-75 kDa. The authors believed that the latter represents a dimerization (agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous mass spectrometric studies confidently identified both recombinant renalase used as a reference and also intracellular and extracellular renalases . However, taking into consideration existing evidence for proteolytic processing of this protein during its translocation to the extracellular space, and the absence of the N‐terminal peptide (1–21) in urinary renalase, we have chosen the peptide EGDCNFVAPQGISSIIK, covering positions 100–116 for subsequent preparation of the synthetic analogue containing stable heavy isotopes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous mass spectrometric studies confidently identified both recombinant renalase used as a reference and also intracellular and extracellular renalases . However, taking into consideration existing evidence for proteolytic processing of this protein during its translocation to the extracellular space, and the absence of the N‐terminal peptide (1–21) in urinary renalase, we have chosen the peptide EGDCNFVAPQGISSIIK, covering positions 100–116 for subsequent preparation of the synthetic analogue containing stable heavy isotopes.…”
Section: Resultsmentioning
confidence: 99%
“…Urinary samples (50 mL) were collected from 12 healthy volunteers (10 males, 2 females, mean age 34 ± 13 years) who gave informed consent for the use of their biomaterial in this study (see Table for details). Quantitative determination of renalase was performed with urinary samples, which were concentrated as described earlier . Briefly, urinary samples (50 mL from each volunteer) were centrifuged for 15 min at 4000 rpm and 4°C (Beckman TJ6 centrifuge, bucket rotor) to remove cells and supernatant proteins were then precipitated with ammonium sulfate (75% saturation at 4°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with results by Pandini et al [6] the target protein product (recombinant nRenalase1) was accumulated in Rosetta (DE3) as an insoluble form in inclusion bodies. The purified protein was not subjected to refolding after purification and was directly used for custom-made generation of polyclonal antibodies, which were successfully used for recent mass spectrometry detection of hRenalase1 in human urine [13]. Table 2 summarizes purification steps of both proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Resultant full-length coding sequences of both hRenalase1 and hRenalase2 were used for expression of the recombinant proteins in E. coli Rosetta (DE3) cells, and hRenalase1 was then used for generation of polyclonal anti-renalase antibodies, which effectively interacted not only with the purified recombinant hRenalase1, but also with hRenalase1 in urine of volunteers [13]. Results of this study indicate that hRenalase2 also interacts with the polyclonal anti-renalase antibodies (Figure 6).…”
Section: Discussionmentioning
confidence: 99%